El Riesgo Financiero y el Consentimiento Indígena - Imai, Shin (2014)
In this article, the authors describe how the International Financial Corporation of the World Bank, and the 77 global financial institutions that have signed on to the Equator Principles, have come to the conclusion that social conflict with indigenous communities needs to be resolved through the application of free, prior, informed and consent. While the requirement to obtain consent of an indigenous people would appear to make it more difficult for extractive industry projects to proceed, theories of dispute resolution developed by the Harvard Negotiation Project suggest that where consent is obtained, it is more likely thatc onflicts will be reduced.